Sulfur-doped nickel oxide thin film as an alternative to Pt for dye-sensitized solar cell counter electrodes - Li, Chang Ming (2013)
A low-cost, sulfur-doped NiO (S–NiO) thin film is electrodeposited on fluorine-doped SnO2 substrate and studied in an iodide-based redox system. High electrochemical activity is present because of a large catalytic surface area and a low charge transfer resistance. A dye- sensitized solar cell with a low-loaded S–NiO counter electrode achieves a power conversion efficiency of 5.04%, close to that of a cell with a conventional platinized electrode.